Changes in impact of HLA class I allele expression on HIV-1 plasma virus loads at a population level over time - Koga, Michiko; Kawana-Tachikawa, Ai; Heckerman, David; Odawara, Takashi; Nakamura, Hitomi; Koibuchi, Tomohiko; Fujii, Takeshi; Miura, Toshiyuki; Iwamoto, Aikichi (Microbiology and immunology, 2010)
HLA class I allele types have differential impacts on the level of the pVL and outcome of HIV-1 infection. While accumulations of CTL escape mutations at population levels have been reported, their actual impact on the level of the pVL remains unknown. In this study HLA class I types from 141 untreated, chronically HIV-1 infected Japanese patients diagnosed from 1995-2007 were determined, and the associations between expression of individual HLA alleles and level of pVL analyzed. It was found that the Japanese population has an extremely narrow HLA distribution compared to other ethnic groups, which may facilitate accumulation of CTL escape mutations at the population level. Moreover while they uniquely lack the most protective HLA-B27/B57, they commonly express the alleles that are protective in Caucasians (A11:10.4%, A26:11.55%, B51:8.6% and Cw14:12.7%). Cross-sectional analyses revealed no significant associations between expression of individual alleles and the level of the pVL. The patients were then stratified by the date of HIV diagnosis and the analyses repeated. It was found that, before 2001, B51+ individuals displayed significantly lower pVL than the other patients (median: 5150 vs. 18,000 RNA copies/ml, P=0.048); however thereafter this protective effect waned and disappeared, whereas no changes were observed for any other alleles over time. These results indicate that, at a population level, some HLA alleles have been losing their beneficial effects against HIV disease progression over time, thereby possibly posing a significant challenge for HIV vaccine development. However such detrimental effects may be limited to particular HLA class I alleles.